PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP TINGKAT KEPATUHAN PENYAJIAN LAPORAN KEUANGAN SESUAI PSAK 1 - Caroline Pujiono, Elsa Imelda (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study is to analyze of a firm’s characteristics, which include the profitability, industry type, and liquidityon the level of compliance in presenting financial statement based on PSAK 1 to the service firm registered in the Indonesian Stock Exchange on the period 2016-2018. The samples in this studytaken using a purposive sampling method. The data in this study is processed by Eviews 10.0, the result shows that the level of compliance in presenting financial statements based on PSAK 1 of Indoneisan companiesis82.55% in average. The regression analysis shows a significant relationship between industry type with the compliance level. The other independent variable, profitability and liquidityinsignificant on the compliance level based on PSAK 1.